1974
DOI: 10.1002/cpt1974152141
|View full text |Cite
|
Sign up to set email alerts
|

Renal action, therapeutic use, and pharmacokinetics of the diuretic bumetanide

Abstract: The diuretic activity of bumetanide has been studied in 16 Glasgow, London, and Sheffield, England Department of Medicine, Western Infirmary, Glasgow, Department of Therapeutics, Westminister Hospital, London, and Department of Pharmacology and Therapeutics, Royal Infirmary, Sheffield Bumetanide (3-n-butylamino-4-phenoxy-5-sulfamoylbenzoic acid, Brinex) is a derivative of metanilamide that displays potent diuretic activity on oral administration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 7 publications
7
51
1
Order By: Relevance
“…The K t values of bumetanide for hOAT2, hOAT3, and hOAT4 were 7.52, 1.59, and 0.31 M, respectively (Hasannejad et al, 2004;Kobayashi et al, 2005), but the affinity of bumetanide for MCT6 (K t value at pH 7.4; 84 M) was lower. The clinical plasma concentration and plasma protein binding of bumetanide were reported to be about 0.27 M and 95%, respectively (Davies et al, 1974;Pentikainen et al, 1977). Consequently, the estimated plasma unbound concentration of bumetanide is 0.014 M, which is lower than K t values of MCT6, hOAT2, hOAT3, and hOAT4.…”
Section: Inhibitory Effects Of Anions and Cations On The Uptake Of ͓ mentioning
confidence: 89%
“…The K t values of bumetanide for hOAT2, hOAT3, and hOAT4 were 7.52, 1.59, and 0.31 M, respectively (Hasannejad et al, 2004;Kobayashi et al, 2005), but the affinity of bumetanide for MCT6 (K t value at pH 7.4; 84 M) was lower. The clinical plasma concentration and plasma protein binding of bumetanide were reported to be about 0.27 M and 95%, respectively (Davies et al, 1974;Pentikainen et al, 1977). Consequently, the estimated plasma unbound concentration of bumetanide is 0.014 M, which is lower than K t values of MCT6, hOAT2, hOAT3, and hOAT4.…”
Section: Inhibitory Effects Of Anions and Cations On The Uptake Of ͓ mentioning
confidence: 89%
“…However IND produced an anticalciuria with very little change in magnesium excretion, other than a slight increase on the first day. These longer term effects on divalent cation excretion differ from the calciuria and magnesuria observed during the acute diuretic phase with both thiazides (Parfitt, 1969) and 'loop' diuretics (Davies et al, 1974).…”
mentioning
confidence: 77%
“…There was no evidence of a dose-response relationship and spontaneous variation from day to day was not assessed. Other workers have shown only small increases in Mgu following single doses of frusemide [81,82] and these did not reach statistical significance. Labeeuw et al [83] using 2 mg methylclothiazide by mouth (placebo, random order) found Mgu to be increased by only 14% whereas the average day to day spontaneous variation was 32% (range 11-60%).…”
Section: Animalsmentioning
confidence: 90%